E JORDANIAN POLITICAL STANCE ON THE RHODES AGREEMENT WITH ISRAEL 1949 – 1950: HISTORICAL ANALYSIS AND ARAB–INTERNATIONAL REACTIONS - MAHAMOUD, Ayman A. (EAST EUROPEAN HISTORICAL BULLETIN, 2025)
The political stance of the Hashemite Kingdom of Jordan on the Rhodes Agreement with Israel (1949) remains a subject of analytical and documentary interest, especially considering the complex Arab-Israeli dynamics in the post-1948 war era. While several Arab states accused Jordan of pursuing a separate peace, the available diplomatic and press records demonstrate a more nuanced and cautious approach adopted by the Jordanian leadership. The purpose of this research is to investigate Jordan’s negotiating strategy during the Rhodes Armistice talks, its interactions with Arab and Western powers, and the media discourse surrounding the agreement. The methodology of this research is based on a historical documentary approach that combines official U.S. and British documents with Egyptian and Jordanian newspaper accounts, in addition to scholarly interpretations from Israeli and Western historians. The scientific novelty сonsists in the reinterpretation of Jordan’s motives and goals during the negotiations, shifting the analysis away from nationalist rhetoric toward a more balanced reading grounded in primary sources. The findings indicate that King Abdullah I pursued the armistice to secure political leverage over Jerusalem and the West Bank, while maintaining an Arab consensus to the extent possible. Both strategic calculations and pressure from Britain, the Arab League, and internal constraints shaped the Jordanian position. Despite accusations of unilateralism, Jordan neither aimed to conclude a full peace treaty nor acted independently of the Arab context but sought instead to consolidate its territorial gains without fully detaching from the broader Arab cause. The conclusion of the study shows that the Rhodes Agreement inaugurated a new phase of legal and political contestation over Palestine, reflecting the interplay between diplomacy, war outcomes, and regional rivalries. Keywords: Rhodes Agreement, Jordan, Israel, 1949 Armistice, Arab League, Egyptian Press, American Documents.